2016
DOI: 10.3389/fnhum.2016.00599
|View full text |Cite
|
Sign up to set email alerts
|

Better Not to Know? Emotion Regulation Fails to Benefit from Affective Cueing

Abstract: Often we know whether an upcoming event is going to be good or bad. But does that knowledge help us regulate ensuing emotions? To address this question, we exposed participants to alleged social feedback that was either positive or negative. On half the trials, a preceding cue indicated the feedback’s affective quality. On the remaining trials, the cue was uninformative. In two different blocks, participants either appraised feedback spontaneously or down-regulated ensuing emotions using a controlled appraisal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…First, targets occurring on a high as compared with a low regularity background elicited a smaller N1, a marginally larger P3 and faster reaction times. A smaller N1 has been previously associated with increased predictability or perceptual fluency ( Robinson et al., 2018 ), whereas a larger P3 and other late positivities have been linked to a number of functions including task relevance ( Squires et al., 1977 ; Johnson Jr and Donchin, 1978 ) and emotional salience ( Hajcak et al., 2010 ; Liu et al., 2016 ; Schirmer and Gunter, 2017 ). Regularity also modulated the frequency tagging response over occipital cortex.…”
Section: Discussionmentioning
confidence: 99%
“…First, targets occurring on a high as compared with a low regularity background elicited a smaller N1, a marginally larger P3 and faster reaction times. A smaller N1 has been previously associated with increased predictability or perceptual fluency ( Robinson et al., 2018 ), whereas a larger P3 and other late positivities have been linked to a number of functions including task relevance ( Squires et al., 1977 ; Johnson Jr and Donchin, 1978 ) and emotional salience ( Hajcak et al., 2010 ; Liu et al., 2016 ; Schirmer and Gunter, 2017 ). Regularity also modulated the frequency tagging response over occipital cortex.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one previous study tested the causal influence of preceding anticipatory information on subsequent regulation of social feedback (Liu, Vanderhasselt, Zhou, & Schirmer, 2016). This study demonstrated that receiving anticipatory information regarding the negative valence of upcoming social feedback facilitated subsequent actual regulation of social feedback.…”
Section: Studymentioning
confidence: 99%
“…This reinterpretation process can potentially benefit from prior anticipatory information processing that likely elicited multiple subjective interpretations, some of which are suitable and more accessible as potential reappraisals. Accordingly, we expected anticipatory information to facilitate the reinterpretation process during reappraisal implementation, manifested in decreased late LPPs (Liu et al, 2016).…”
Section: Studymentioning
confidence: 99%
“…We are aware of only two studies exploring our first question regarding influence of the presence (vs. absence) of unbiased anticipatory information on subsequent down-regulation. In the first study, participants received or did not receive unbiased anticipatory information regarding the valence of upcoming social feedback (i.e., a negative or positive emoticon, or question mark), prior to meaning-modulation down-regulation (Liu, Vanderhasselt, Zhou, & Schirmer, 2016). Congruent with the literature on anticipatory information influences on cognition, results showed that the presence (vs. absence) of anticipatory information generally enhanced attention to unpleasant social feedback (e.g., “unattractive”), manifested in increased early-LPPs.…”
Section: How Anticipatory Information Shapes Emotion Regulation: a Ne...mentioning
confidence: 99%